Dermoscopic analysis of the skin of healthy warmblood horses: a descriptive study of 34 cases in Italy. Issue 2 (1st November 2017) - Legnani, Sara; Zini, Eric; Roccabianca, Paola; Funiciello, Beatrice; Zanna, Giordana
Abstract : Background: Dermoscopy is a diagnostic tool that has been introduced into small animal dermatology for the evaluation of hair and the skin surface. To the best of the authors' knowledge, the use of this technique on horses and the dermoscopic appearance of equine hair and skin have yet to be reported. Hypothesis/objectives: To assess the feasibility of dermoscopy, and to describe hair and skin surface features of healthy warmblood horses. Animals: Thirty four client‐owned, healthy adult horses. Methods: Six body regions (head, neck, dorsal thorax, ventral thorax, croup and mane) were examined with a smartphone‐attached, hand‐held polarized light dermoscope at 20‐fold magnification. Smartphone‐collected images were evaluated to determine the overall hair density, large and thin primary hair densities and diameters, and skin surface characteristics. Software was used to measure large and thin primary hair shaft thickness. Comparisons between body regions, breeds and sexes were made. Results: Dermoscopic examination of the equine skin surface was feasible and easy to perform. At 20‐fold magnification thick, straight hair shafts emerging from single follicular openings were observed. In between these, thinner straight hair shafts were present in all evaluated regions. Hair shafts of the head and the mane were significantly thicker but less dense compared to other regions. Skin pigmentation and variable perifollicular discolouration were present. Conclusions: Dermoscopy may represent a valuable technique for the dermatological examination of the equine patient. Abstract : Background – Dermoscopy is a diagnostic tool that has been introduced into small animal dermatology for the evaluation of hair and the skin surface. To the best of the authors' knowledge, the use of this technique on horses and the dermoscopic appearance of equine hair and skin have yet to be reported.Hypothesis/objectives – To assess the feasibility of dermoscopy, and describe hair and skin surface features of healthy warmblood horses.Conclusions – Dermoscopy may represent a valuable technique for the dermatological examination of the equine patient.